2013
DOI: 10.1177/0025802413502783
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: A study of elderly unnatural deaths in medico-legal autopsies at Lucknow locality

Abstract: The main aim of this study was to determine the causes and epidemiological aspects of unnatural deaths in the elderly. Data were collected on 4405 male and female victims of unnatural deaths aged 50 years or more from the total number of 21,235 autopsies performed in King George's Medical University, Lucknow, India over a 5-year period, from 2008 to 2012. There were 3165 male victims and 1240 female victims. Unnatural deaths were higher in rural (64%) than in urban (37%) areas. Accidental deaths were the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
0
17
2
1
Order By: Relevance
“…Unnatural deaths and specifically traffic accidents were higher in urban areas in this study. In contrast with these results were those obtained by Kumar and Verma in their study conducted in India (Kumar and Verma 2014).…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…Unnatural deaths and specifically traffic accidents were higher in urban areas in this study. In contrast with these results were those obtained by Kumar and Verma in their study conducted in India (Kumar and Verma 2014).…”
Section: Discussioncontrasting
confidence: 91%
“…The poisoning of the elderly, unlike our study, is reported to be more often suicidal than accidental in studies carried out in India and Norway (Kumar and Verma 2014;Eilertsen et al 2006). We observed that accidental poisoning was especially caused by carbon monoxide and due the increased use of braziers in winter.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations